Hubungan Faktor Social Area (Kebisingan), Faktor Individual Area (Karakteristik Individu), Dan Faktor Work Area (Beban Kerja Dan Hubungan Interpersonal) Terhadap Stres Kerja Pada Pekerja Departemen Spinning Di PT. Acryl Textile Mills, Tangerang Tahun 2024 - Aprilia Kurniawan, Fadillah; Saputra, Atang; Riyanto, Agus (CV. Multi Kreasi Media, 2024)
Work stress is a pressure that arises from the work environment and individual characteristics of workers that can affect the thought process, way of working, emotions and physical condition of a person. If work stress occurs at a high level and is not properly controlled, it can reduce worker productivity. Work stress can be influenced by several factors, including social area factors, individual area factors, and work area factors. This study aims to find out